The newsmakers - Wiehl, Lis W.; Stuart, Sebastian (Wiehl, Lis W. Newsmakers novels., 2016)
"What if it turns out that the newsmakers are actually making the news happen? Television reporter Erica Sparks has just landed her dream job at Global News Network. Beautiful, talented, and ambitious, Erica grew up dirt poor, worked her way through Yale, and is carrying a terrible secret. She moves to Manhattan to join GNN, leaving Jenny, her adored 7-year-old daughter, in the custody of her ex-husband. Erica's producer at the network, Greg Underwood, is handsome and compelling. Scarred by her divorce, Erica is wary of romance, but there's no denying the mutual attraction. On one of her first assignments, Erica witnesses a horrific Staten Island ferry crash. Then she lands a coveted interview with presumptive presidential nominee Kay Barrish. During the interview Barrish collapses. Erica valiantly tries to save her with CPR. The footage rivets the world--GNN's ratings soar and Erica is now a household name. But she's troubled. What a strange coincidence that both events should happen on her watch. It's almost as if they were engineered. Is that possible? Erica's relentless pursuit of the truth puts her life and that of her daughter in danger. Her investigation leads her into the heart of darkness--where the future of our democracy is at stake"--